PENGARUH PERUBAHAN MEREK NATIONAL MENJADI PANASONIC TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI WILAYAH PEMASARAN KELURAHAN SUMUR BATU TELUK BETUNG UTARA BANDAR LAMPUNG - Ratnawati, Eva; -, Herlina (Jurnal Manajemen dan Keuangan, 2009)
Rebranding of National to Panasonic is included name, logo, design and slogan changing. Rebranding make the product image changes and the consumer have to recognize the new brand from the brand before. The consumer perception of rebranding will affect the psychological response which performed by buying decision. Problem of the research shown the sales was decreased in market region of Bandar Lampung as long as five years.The research was purposed to know the dominant variable which influence to the consumer buying decision in market region of Kelurahan Sumur Batu Teluk Betung Utara Bandar Lampung. The method of research used descryptif to describe the phenomena. Population of the research is 96 head families in kelurahan Sumur Batu which chosen by cluster sampling. The data analysis used multiple regressionsKeywords: rebranding, consumer buying decision